Motion Control of Mechanical Systems with Backlash - Moradian, Khadijeh; Tavakoli Afshari, Saeed (Mechanical Technology and Engineering Insights, 2024)
Backlash is a mechanical interaction which occurs with clearance between structural parts of a mechanical system. The clearance causes noncompletion, nonuniform rotation or displacement of structure parts. Due to the clearance errors in positioning and motion of structure parts occur. In this paper, a software based solution for mechanical systems with backlash is presented. To achieve accurate speed control, a Proportional-Derivative (PD) compensator is combined with a Proportional-Integral (PI) controller. The correct controller is adopted by a Genetic Algorithm (GA). As the criteria for the system, first, overshoot, second, error performance index are considered. According to ITAE criterion, there exists very low oscillations in the step response of the system. This indicates good system stability.